Scour profiles at downstream of cascades - Tuna, M. C.; Emiroglu, M. E. (Sharif Univ Technology, 2011)
A study was conducted to simplify and broaden the procedures for estimating scour dimensions at the downstream of cascades. There are many studies about energy dissipation, aeration and oxygen transfer in stepped-channel chutes and cascades. There is little attention paid to the scour downstream of the stepped chutes and their downstream scour hole geometry. Measurements were taken to obtain a scour hole profile in the equilibrium state of the scour, the value of the maximum depth of the scour, the location of the maximum scour depth and the length of the scour hole. It was also found that step geometry, stepped chute angle, downstream water level and sill types of a stilling basin are very important parameters for the geometry of the scour hole. (C) 2011 Sharif University of Technology. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Cascade; Stepped chute; Local scour; Nappe flow; Skimming flow; Transition flow; Flow regime